Simeons døde hund - Graarup, Kasper (Religionsvidenskabeligt Tidsskrift, 1998)
Symeon of Emesa is a holy fool. When holy fools appear in public, they behave as if they were mad, but at night when they are alone with God, they act as "normal" ascetics: they pray and cry and prostate themselves. When Symeon came to Emesa, he tied a dead dog to his belt and dragged it through the city gate. In my view, Symeon with his dead dog and idiotic and enigmatic behaviour is to be understood in relation to the passion of Christ. Holy foolishness is an ascetic practice, which is located and performed in the moral wilderness of the city. When anchoritic practices of asceticism take place in the physical wilderness of the desert or other remote (from civilisation) regions, the ascetic role model is Jesus in the desert. When the ascetic is a holy fool of the city, the model is Jesus in Jerusalem. When the anchoritic ascetics perform, their bodies, as well as their environment (the desert), are functioning as graphic and physical testimonies to the anchorites' virtuous souls. When the holy fools perform, their bodies are similarly a part of the fluid vanity of their environment: the city. But neither city nor body has any graphic equivalence to the holy fool's soul, which is the direct opposite of his body. The dog belonging to Simeon of Emesa is to be understood in the light of this relationship between soul and body, i.e., the dog is to be understood in relation to Christian virtues regarding asceticism, in particular holy foolishness. The significance of the dog does not necessarity depend on internal references to neither cynicism, as Derek Krueger would maintain, nor to Greek or Egyptian gods, as is the opinion of Ewald Kislinger. The dead dog is a symbol of Symeon's dead body.